A Thousand and One Names of Polish Translation Enterprises in the Lower Silesia Region. Exploring the Polish REGON database - Kuźnik, Anna (Acta Neophilologica, 2024)
This article examines the formal characteristics and names of translation enterprises operating in the Lower Silesia region in 2022. The data on the enterprises were drawn from the Polish official register of economic entities, i.e. REGON database. The conceptual framework is built on three fields: (1) developments in the field of translation & interpreting studies (T&IS); (2) linguistic studies in onomastics on chrematonyms/ergonyms; (3) economic and legal conditions of running businesses in Poland. The results obtained in this study offer comprehensive insights into the economic situation of Polish translation enterprises and suggest main criteria for the future sample selection: in terms of their legal and economic strength, and in terms of translational profile consistency expressed through the lexicon used in the identifying segments of their names in order to designate their core business.